Behavioral Counseling Approach with Self Management Techniques to Increase Achievement Motivation in Underachiever Students - Negari, Ida Ayu Putu Prahasti; Umam, Muhamad Safiul; Suranata, Kadek; Dharmayanti, Putu Ari (Bisma The Journal of Counseling, 2024)
Achievement motivation is an internal drive that drives individuals to achieve success in both academic and non-academic fields. In underachiever students, achievement motivation is very important because it activates untapped potential, encourages the development of learning skills, increases mental toughness, creates self-confidence, and independence. One of the effective counseling approaches in increasing achievement motivation in underachiever students is the behavioral counseling approach using self-management techniques. The purpose of this study was to test the effectiveness of the behavioral counseling approach using self-management techniques to increase achievement motivation in underachiever students. The design of this study was to use a one group pretest-posttest design with a population of 430 seventh grade junior high school students. Sampling used random sampling techniques and random class as an intact group, so that class VII.4 was obtained as a research sample. To test empirical validity, it was analyzed using the product moment correlation formula, while to test instrument reliability, it was analyzed using the Cronbach Alpha formula. Statistical tests used the T-test test to determine the effectiveness of the treatment that had been carried out. H0 is rejected if t count > t table. H0 is accepted if t count ≤ t table. Based on the H1 t-test, the calculated t was 11.131 while the t-table with db N-1 = 40 – 1 = 39 and a significance level of 5% (0.05) was 1.684, so it can be concluded that the behavioristic counseling approach with self-management techniques is effective in increasing achievement motivation in underachiever students.